2003
DOI: 10.1289/ehp.5563
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of recreational health risk in coastal waters based on enterococcus densities and bathing patterns.

Abstract: We constructed a simulation model to compute the incidences of highly credible gastrointestinal illness (HCGI) in recreational bathers at two intermittently contaminated beaches of Orange County, California. Assumptions regarding spatial and temporal bathing patterns were used to determine exposure levels over a 31-month study period. Illness rates were calculated by applying previously reported relationships between enterococcus density and HCGI risk to the exposure data. Peak enterococcus concentrations occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 18 publications
2
37
1
Order By: Relevance
“…horizontal line), peaking at about 60 excess illnesses per 1000 bathers; these illness attack rates are in the range estimated by other researchers for the Huntington Beach area (26). Now-casts for the exceedence probability (fourth panel) exhibit spring-neap cycling, and importantly, periods of high exceedence probability (e.g., Pex|l > 0.2) generally coincide with single-sample violations (compare second and fourth panels, Figure 5).…”
Section: Toward An Analog Public Health Advisory Systemsupporting
confidence: 62%
“…horizontal line), peaking at about 60 excess illnesses per 1000 bathers; these illness attack rates are in the range estimated by other researchers for the Huntington Beach area (26). Now-casts for the exceedence probability (fourth panel) exhibit spring-neap cycling, and importantly, periods of high exceedence probability (e.g., Pex|l > 0.2) generally coincide with single-sample violations (compare second and fourth panels, Figure 5).…”
Section: Toward An Analog Public Health Advisory Systemsupporting
confidence: 62%
“…Our estimates for the same stretch of shoreline are higher (68,011 and 87, 513 excess GI based on models C and K, respectively). Not only did we use a different measure of illness (GI vs. HCGI) we also used a Monte Carlo scheme to estimate ENT on unsampled days whereas Turbow et al (18) used linear interpolation, and we used higher, empirically determined (18) estimate to determine that the health costs of excess GI at the same beaches were $1.2 million. Our health cost estimates are higher ($2.3 and $2.9 million for models C and K, respectively), due to the higher incidence of ilness predicted by our models.…”
Section: Discussionmentioning
confidence: 99%
“…ENT densities on unsampled days during 2000 were estimated by randomly sampling from the appropriate seasonal distribution. Because day-to-day ENT concentrations at marine beaches are weakly correlated and variable (17), we chose not to follow the estimation method of Turbow et al (18) who assumed a linear relationship between day-to-day ENT densities at two CA beaches. Comparisons between the Monte Carlo method and a method that simply used the monthly arithmetic average ENT density indicated the two provided similar results (data not shown).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have reported usage frequency for swimmers and non-swimmers based on records of lifeguards stands, 3,4 or conducted randomized trials for evaluating exposure differences between bathers and non-bathers. 5 At least one study used aerial photographs in conjunction with interviews of state officials.…”
Section: Introductionmentioning
confidence: 99%